3D numerical modelling of twisting cracks under bending and torsion of skew notched beams. (1st May 2017) - Benedetti, Lorenzo; Cervera, Miguel; Chiumenti, Michele
Highlights: Mixed FEM is applied to mode III and mixed mode failure in quasi-brittle materials. A mixed strain displacement formulation is used in plasticity and continuum damage. The material behavior is described via Rankine and Drucker-Prager failure criteria. Exploiting compatibility conditions it is possible to reduce the computational time. Numerical results show good agreement with experiments on skew-notched beams. Abstract: The testing of mode III and mixed mode failure is every so often encountered in the dedicated literature of mechanical characterization of brittle and quasi-brittle materials. In this work, the application of the mixed strain displacement ε - u finite element formulation to three examples involving skew notched beams is presented. The use of this FE technology is effective in problems involving localization of strains in softening materials. The objectives of the paper are: (i) to test the mixed formulation in mode III and mixed mode failure and (ii) to present an enhancement in terms of computational time given by the kinematic compatibility between irreducible displacement-based and the mixed strain-displacement elements. Three tests of skew-notched beams are presented: firstly, a three point bending test of a PolyMethyl MethaAcrylate beam; secondly, a torsion test of a plain concrete prismatic beam with square base; finally, a torsion test of a cylindrical beam made of plain concrete as well. To describe the mechanical behavior of the material in the inelastic range, Rankine and Drucker-Prager failure criteria are used in both plasticity and isotropic continuum damage formats. The proposed mixed formulation is capable of yielding results close to the experimental ones in terms of fracture surface, peak load and global loss of carrying capability. In addition, the symmetric secant formulation and the compatibility condition between the standard irreducible method and the strain-displacement one is exploited, resulting in a significant speedup of the computational procedure.